Educating for Well-being in Law: Positive Professional Identities and Practice edited by Caroline Strevens and Rachael Field - Mark Seton (Bond Law Review)
_Educating for Well-Being in Law: Positive Professional Identities and Practice_ provides both an inspiring and pragmatically grounded set of accounts of what has been done, and could be done to generate positive professional identities and practices in the legal profession.